Understanding corporate concerns. Barriers and challenges in corporate–start-up collaboration - Michal Banka; Norbert Chmiel; Mariusz Kostrzewski; Magdalena Marczewska; Arkadiusz Michal Kowalski; Katarzyna Sedkiewicz; Mariusz Salwin (Journal of Open Innovation: Technology, Market and Complexity)
Despite increasing awareness of the benefits of partnerships with start-ups, corporates are often hesitant to collaborate due to perceived barriers, resulting in failed or suboptimal collaborations. This paper explores and assesses the key barriers that hinder corporates from successfully collaborating with startups. Based on a CAWI interviews with corporations, it evaluates both the significance and the severity of these obstacles, as well as the challenges involved in establishing effective partnerships. Additionally, the study examines how various corporate characteristics—such as company size, experience with startups, strategic approaches, and methods of engagement—impact the success of these collaborations. The findings reveal that corporates face significant challenges in partnering with startups. Major barriers include difficulties in identifying suitable startups, a lack of understanding of startup innovations, and concerns over financial risks associated with startup projects. Other obstacles, though less prominent, include fears of reputational damage if collaborations fail and limited support from corporate leadership for engaging with startups. This research highlights the need for enhanced strategies and knowledge-sharing to overcome these barriers, ultimately leading to more effective corporate-startup collaborations. This paper makes a key contribution by filling a significant research gap in the evaluation of barriers to corporate-startup collaborations, particularly by identifying new and unexplored obstacles that have not been previously documented in the literature. By expanding the catalogue of known barriers and analyzing corporate characteristics that affect collaboration outcomes, the study offers valuable insights for improving strategies and fostering more successful partnerships between corporates and startups.